EFFECT OF DIFFERENT TYPES OF IRRIGATION AND GROWING METHODS ON GROWTH, YIELD ANDWATER-USE EFFICIENCY OF TOMATO (LYCOPERSICON ESCULENTUM MILLER) - G. V. SUBBA REDDY; D. V. PATIL; B.SRIHARI RAO; B. NAGENDRAPRASAD (The Bioscan, 2015)
A two year field study was conducted during 2012-2013 and 2013-2014 on light textured soils of BCT- KVK Visakhapatnamdistrict to investigate the effect of different types of irrigation and growing methods on growth, yield, water-use efficiency and economics of tomato (Lycopersicon esculentum Miller). Drip + polythene mulch + trellising given maximum values for fruit yield (62.21 t/ha), plant height (91.22 cm), fruit weight (88.33 g), plant dry matter (49.32g) and less weed growth (6.12 gm-2) compared to drip + polythene mulch and drip alone. Highest water use efficiency (1.44) was observed in drip + polythene mulch + trellising followed by drip + polythene mulch (1.26). Use of black polyethylene mulch + drip + trellising recorded significantly highest net income (161134 Rs./ha). In case of surface irrigation, furrow + black polythene mulch + trellising recorded highest fruit yield (43.82 t/ha), fruit weight (83.33 g), plant height (83.32 cm) and plant dry matter (41.32 g) followed by furrow + black polythene mulch (35.23 t/ha, 75.62 g, 75.66 cm,36.34g). Less weed growth was observed with furrow + polythene mulch + trellising (30.23gM-2) and furrow + black polythene mulch (30.36 gM-2) when compared to control (62.76 gM-2). Highest net returns (102708 Rs./ha) and benefit cost ratio(2.41) recoded with furrow + black polythene mulch + trellising. Among all the treatments drip + black polythene mulch + trellising recorded highest values for all the parameters.